The land of stories - The Enchantress returns - Colfer, Chris 1990- (Little, Brown, 2013)
Against the will of their grandmother, twins Alex and Conner must find their own way into the Land of Stories to rescue their mother and save the fairy tale world from the greatest threat it has ever faced...the return of the Enchantress who cursed Sleeping Beauty
Keywords: Fairy tales; Characters in literature; Magic; Brothers and sisters; Twins; Youths' writings; Jugendbuch